Muslim Custodians of Jewish Spaces in Morocco Drinking the Milk of Trust - Driver, Cory Thomas Pechan (Contemporary Anthropology of Religion, 2018)
Exploring the roles of Muslim guards and guides in Jewish cemeteries in Morocco, Cory Pechan Driver suggests that these custodians use performances of ritual and caring acts for Jewish graves for multiple reasons. Imazighen [Berbers] stress their close ties with Jews in order to create a moral self intentionally separate from the mono-ethically and mono-religiously Muslim Morocco. Other subjects, and particularly women, use their ties with Jewish sites to harness power and prestige in their communities. Others still may care for these grave sites to express grief for a close Jewish friend or adoptive family. In examining these motives, Driver not only documents the flow of material and spiritual capital across religious lines, but also moves beyond Muslim memory of the past on the one hand and Jewish existential dread of the future on the other to think about the Muslim/Jewish present in Morocco.